قواعد التهيئة العمرانية في التشريع الجزائري - زغودي، عمر; قلوشة، سامية (جامعة عمار ثليجي بالأغواط - كلية الحقوق والعلوم السياسية, 2023)
إن مجال التعمير يعكس مدى تقدم الدولة أو تخلفها؛ ولهذا نجد مفارقات في سياسات الدولة في ميدان البناء وانه يستند إلى أدوات منهجية تدعمه وتوجه مساره بما يحقق الاكتفاء والتنمية المحلية، ويرسم معالم الانسجام في العمران أي المحافظة على جمال المدن بأحيائها وأريافها وطرقها، إن الدراسة تهدف إلى التعرف على الآليات القانونية والتنظيمية للتخطيط العمراني من أجل ضمان تنمية مستدامة وإعادة التأطير لمجال التنمية في ميدان العمران للوصول إلى تهيئة عمرانية تحافظ على رونق المحيط وتعكس هوية الجزائر The field of reconstruction reflects the progress or backwardness of the state; And for this we find paradoxes in the state’s policies in the field of construction and that it is based on methodological tools that support it and direct its path in order to achieve sufficiency and local development, and draw the features of harmony in urbanization, that is, to preserve the beauty of cities with their neighborhoods, countryside and roads. The study aims to identify the legal and regulatory mechanisms for planning Al-Omrani in order to ensure sustainable development and reframing the field of development in the field of urbanization in order to reach an urban setting that preserves the splendor of the ocean and reflects the identity of Algeria
Keywords: الإنشاءات العمرانية -- التخطيط العمراني -- التشريع الجزائري -- التنمية المحلية